Do not resuscitate decisions: discussions with patients - Schade, S. G. (Journal of medical ethics, 1989)
The problem of psychological pain caused by discussions of do not resuscitate status with patients is addressed. Case histories of patients with such distress are given. We propose that not all patients should be informed of their do not resuscitate status, that the information about such status be given incrementally, and that the giving of further information be guided by the patient's reaction to earlier information. While some affirm the duty of the physician always to inform the patient about his or her do not resuscitate status, we affirm the duty of the physician to determine whether the patient wishes to enter into this discussion.